The effects of traditional and enforced stopping speed and agility training on multidirectional speed and athletic function - Lockie, R. G.; Schultz, A. B.; Callaghan, S. J.; Jeffriess, M. D. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the effects of a traditional speed and agility training program (TSA) and an enforced stopping program emphasizing deceleration (ESSA). Twenty college-aged team sport athletes (16 males, 4 females) were allocated into the training groups. Pretesting and posttesting included: 0-10, 0-20, 0-40 m sprint intervals, change-of-direction, and acceleration test (CODAT), T-test (multidirectional speed); vertical, standing broad, lateral, and drop jumps, medicine ball throw (power); Star Excursion Balance Test (posteromedial, medial, anteromedial reaches; dynamic stability); and concentric (240°/s) and eccentric (30°/s) knee extensor and flexor isokinetic testing (unilateral strength). Both groups completed a 6-week speed and agility program. The ESSA subjects decelerated to a stop within a specified distance in each drill. A repeated measures analysis of variance determined significant (p < 0.05) within- and between-group changes. Effect sizes (Cohen's d) were calculated. The TSA group improved all speed tests (d = 0.29-0.96), and most power tests (d = 0.57-1.10). The ESSA group improved the 40-m sprint, CODAT, T-test, and most power tests (d = 0.46-1.31) but did not significantly decrease 0-10 and 0-20 m times. The TSA group increased posteromedial and medial excursions (d = 0.97-1.89); the ESSA group increased medial excursions (d = 0.99-1.09). The ESSA group increased concentric knee extensor and flexor strength, but also increased between-leg knee flexor strength differences (d = 0.50-1.39). The loading associated with stopping can increase unilateral strength. Coaches should ensure deceleration drills allow for appropriate sprint distances before stopping, and athletes do not favor 1 leg for stopping after deceleration.